2023
DOI: 10.1111/jopr.13654
|View full text |Cite
|
Sign up to set email alerts
|

The influence of horizontal glass fiber posts on fracture strength and fracture pattern of endodontically treated teeth: A systematic review and meta‐analysis of in vitro studies

Abstract: Purpose This systematic review and meta‐analysis aimed to summarize available evidence regarding the effect of horizontal glass fiber posts (HGFPs) on fracture strength and fracture pattern of endodontically treated teeth (ETT) compared to controls without HGFP. The review protocol was registered on the OSF registries. Methods Literature searches were conducted in MEDLINE/PubMed, Scopus, Web of Science, Embase, Google Scholar, and ProQuest for all relevant studies published up to February 2022. All in vitro st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Since the materials and preparation techniques used are different, no study directly compares to the results of this study. However, these findings are consistent with a recent systematic review and meta-analysis by Abdulrab et al [31], which investigated the effect of horizontal glass fiber posts on fracture strength.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since the materials and preparation techniques used are different, no study directly compares to the results of this study. However, these findings are consistent with a recent systematic review and meta-analysis by Abdulrab et al [31], which investigated the effect of horizontal glass fiber posts on fracture strength.…”
Section: Discussionsupporting
confidence: 92%
“…The transfixed technique is described as creating grooves in the buccal and palatal/lingual cusps to horizontally insert the post [30], which has also been labeled as the transcoronal [17] or the horizontal fiber post [31] technique. In the studies where this technique was used with different materials, such as polyethylene fibers [17], a glass fiber post [32], or a zirconia post [30], it was found that this technique increased the fracture resistance of teeth.…”
Section: Discussionmentioning
confidence: 99%